Best of Both Worlds: Design and Evaluation of an Adaptive Delegation Interface. (September 2013) - de Visser, Ewart; Kidwell, Brian; Payne, John; Lu, Li; Parker, James; Brooks, Nathan; Chabuk, Timur; Spriggs, Sarah; Freedy, Amos; Scerri, Paul; Parasuraman, Raja
The proliferation of unmanned aerial vehicles (UAVs) in civil and military domains has spurred increasingly complex automation design for augmenting operator abilities, reducing workload, and increasing mission effectiveness. We describe the Adaptive Interface Management System (AIMS), an intelligent adaptive delegation interface for controlling and monitoring multiple unmanned vehicles, with a mixed-initiative team model language. A study was conducted to assess understanding of this model language and whether participants exhibited calibrated trust in the intelligent automation. Results showed that operators had accurate memory for role responsibility and were well calibrated to the automation. Adaptive automation design approaches like the one described in this paper can be useful to create mixedinitiative human-robot teams.